Archaeology and Biogeography of the Western Pond Turtle (Actinemys marmorata) in the Puget Sound Region - Fisher, Jacob (Ethnobiology Letters, 2018)
The modern distribution of the western pond turtle (Actinemys marmorata) is discontinuous, with a historic but extirpated population in the Puget Sound region that was isolated from populations south along the Columbia River. To better understand this distribution, a review of the archaeological literature for the Puget Sound region was conducted to determine the prehistoric biogeography of the species in the Puget Sound area. Western pond turtles are nearly absent from the regional archaeological record, represented at best by four tentative specimens. This may be explained by extremely low population levels throughout the Holocene at the northernmost extent of its range.